Tunisia at its crossroad: The role of a local development contextualised entrepreneurship training at universities. (August 2015) - Kuhle, Holger
Tunisia faces major problems of unemployment or precariously employed. As in many countries, entrepreneurship has also found its way into higher education in Tunisia. It is often said here as elsewhere that the universities have a crucial role as potential drivers for a locally inspired and contextualised promotion of entrepreneurship. Today, the graduate business start-up support arrangements within the universities or at the public promotion agencies are strongly focused on the early stages of business launch. They neglect later support to overcome critical thresholds during business development and growth that contribute to ensuring longer term survival and business development. Also, the relationship between these support services within the various regions and the respective business communities is not well established. The local economic context varies between economically strong coastal areas and poorly developed interior regions. The lesson is that Tunisian higher education institutions can play an essential role in creating jobs for graduates and building a dynamic base of growth-oriented businesses if they recognise entrepreneurship promotion as a strategic objective and develop appropriate activities in close relation with their local economic context.